Stereochemical conversion of C3‐vinyl group to 1‐hydroxyethyl group in bacteriochlorophyll c by the hydratases BchF and BchV: adaptation of green sulfur bacteria to limited‐light environments. Issue 6 (1st October 2015) - Harada, Jiro; Teramura, Misato; Mizoguchi, Tadashi; Tsukatani, Yusuke; Yamamoto, Ken; Tamiaki, Hitoshi
Summary: Photosynthetic green sulfur bacteria inhabit anaerobic environments with very low‐light conditions. To adapt to such environments, these bacteria have evolved efficient light‐harvesting antenna complexes called as chlorosomes, which comprise self‐aggregated bacteriochlorophyll c in the model green sulfur, bacterium C hlorobaculum tepidum . The pigment possess a hydroxy group at the C3 1 position that produces a chiral center with R ‐ or S ‐stereochemistry and the C3 1 ‐hydroxy group serves as a connecting moiety for the self‐aggregation. C hlorobaculum tepidum carries the two possible homologous genes for C3‐vinyl hydratase, bch F and bch V . In the present study, we constructed deletion mutants of each of these genes. Pigment analyses of the bch F ‐inactivated mutant, which still has BchV as a sole hydratase, showed higher ratios of S ‐epimeric bacteriochlorophyll c than the wild‐type strain. The heightened prevalence of S ‐stereoisomers in the mutant was more remarkable at lower light intensities and caused a red shift of the chlorosomal Qy absorption band leading to advantages for light‐energy transfer. In contrast, the bch V ‐mutant possessing only BchF showed a significant decrease of the S ‐epimers and accumulations of C3‐vinyl BChl c species. As trans‐ criptional level of bch V was upregulated at lower light intensity, the C hlorobaculum tepidum adapted to low‐light environments by control of the bch V transcription. Abstract : Green sulfur bacteria possess a number of bacteriochlorophyll c pigments in light‐harvesting antenna systems. The pigment molecule has a 3‐1‐hydroxyethyl group that produces a chiral center with 3 1 R ‐ or S ‐stereochemistry. The biosynthetic ratio of these epimers is altered by two hydratases, BchF and BchV, to adapt to environmental light intensity. The sole BchV can synthesis S ‐epimeric pigments as well as R ‐epimers, and has significant role under low‐light conditions.